A Canadian Response to the Pursuit of Global Sustainability Reporting Standards*. (12th July 2022) - Elkins, Hamilton; Entwistle, Gary
ABSTRACT: As business, government, and society continue to emphasize the importance of sustainability—both of individual organizations and of the natural world—accounting standard‐setting bodies want to be part of the process. In September 2020, in response to "urgent and growing demand" for more "consistent and comparable" sustainability reporting, the IFRS Foundation (the Foundation) released for comment a Consultation Paper on Sustainability Reporting. In the paper, the Foundation proposed the creation of a Sustainability Standards Board (SSB), which it would oversee alongside the IASB. The SSB would become, de facto, the global sustainability reporting standard setter. The Foundation received 577 responses to its proposal. These responses came from around the world and from a wide range of stakeholders. Thirty‐eight of the responses came from Canada. This study profiles the Canadian responses, contrasting them with the wider set of worldwide responses. Some uniquely Canadian features include user responses from a large number of pension funds and preparer responses solely from the energy sector. There was also a significant response from the Canadian accounting community, including from the full set of Canadian standard‐setting organizations. Five auditors general also responded. Overall, Canadian respondents supported both globalized sustainability reporting standards and the Foundation's creation of the SSB. This support aligns Canada's response with the worldwide response. RÉSUMÉ: Réponse canadienne à la création de normes mondiales sur l'information relative à la durabilité Alors que les entreprises, les gouvernements et la société continuent de mettre l'accent sur l'importance de la durabilité, à la fois des organisations individuelles et du milieu naturel, les organismes de normalisation comptable souhaitent participer au processus. En septembre 2020, en réponse à la « demande urgente et croissante » d'information relative à la durabilité plus « uniforme et comparable », l'IFRS Foundation (la Fondation) a publié aux fins de commentaires un document de consultation sur le sujet. Dans ce document, la Fondation propose la création d'un conseil des normes sur la durabilité, qu'elle chapeauterait parallèlement à l'IASB. Ce conseil deviendrait par le fait même l'organisme de normalisation de l'information relative à la durabilité à l'échelle mondiale. La Fondation a reçu 577 réponses à sa proposition, formulées par un vaste éventail de parties prenantes de partout dans le monde, dont 38 du Canada. La présente étude dresse un portrait des réponses canadiennes, en les comparant à l'ensemble des réponses reçues d'ailleurs. Parmi les caractéristiques propres aux réponses canadiennes, mentionnons le grand nombre de réponses fournies par des régimes de retraite du côté des utilisateurs et le fait que celles fournies par des préparateurs provenaient exclusivement du secteur énergétique. La communauté comptable du Canada a aussi répondu en grand nombre, y compris tous les organismes d'établissement de normes canadiens. Cinq vérificateurs généraux ont également fait parvenir leurs commentaires. Dans l'ensemble, à l'image du reste du monde, les répondants canadiens appuyaient l'établissement de normes mondiales sur l'information relative à la durabilité ainsi que la création d'un conseil des normes par la Fondation.